Learned self-regulation of the lesioned brain with epidural electrocorticography - Gharabaghi, Alireza; Naros, Georgios; Khademi, Fatemeh; Jesser, Jessica; Spüler, Martin; Walter, Armin; Bogdan, Martin; Rosenstiel, Wolfgang; Birbaumer, Niels (Frontiers in Behavioral Neuroscience, 2014)
Introduction: Different techniques for neurofeedback of voluntary brain activations are currently being explored for clinical application in brain-related disorders. One of the most frequently used approaches is the self-regulation of oscillatory signals recorded with electroencephalography (EEG). Many patients are, however, not in a position to use such tools. This could be due to the specific anatomical and physiological properties of the patient's brain after the lesion, as well as to methodological issues related to the technique chosen for recording brain signals. Methods: A patient with extended ischemic lesions of the cortex was unable to gain volitional control of sensorimotor oscillations when using a standard EEG-based approach. We provided him with a neurofeedback set-up with which his brain activity could be recorded from the epidural space by electrocorticography (ECoG). Results: Ipsilesional epidural recordings of field potentials facilitated learned self-regulation of brain oscillations in an online closed-loop paradigm and allowed swift and reliable neurofeedback training for a period of four weeks on a daily basis. Conclusion: Epidural implants may decode and train brain activity even when the cortical physiology is distorted following severe brain injury. Such practice would allow for reinforcement learning of preserved neural networks and may well provide restorative tools for those patients who are worst afflicted.